2019
DOI: 10.1111/tpj.14509
|View full text |Cite
|
Sign up to set email alerts
|

The coordinated action of PPR4 and EMB2654 on each intron half mediates trans‐splicing of rps12 transcripts in plant chloroplasts

Abstract: The pentatricopeptide repeat proteins PPR4 and EMB2654 have been shown to be required for the transsplicing of plastid rps12 transcripts in Zea mays (maize) and Arabidopsis, respectively, but their roles in this process are not well understood. We investigated the functions of the Arabidopsis and Oryza sativa (rice) orthologs of PPR4, designated AtPPR4 (At5g04810) and OsPPR4 (Os4g58780). Arabidopsis atppr4 and rice osppr4 mutants are embryo-lethal and seedling-lethal 3 weeks after germination, respectively, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 70 publications
1
44
0
Order By: Relevance
“…In contrast, defects in Rps8 translation due to loss of PGR3 in not4a likely explains why ribosome depletion is specific to the 30S subunit, since protein complex stoichiometries are highly regulated, with the inability to assemble complete complexes often leading to degradation of orphan subunits (Juszkiewicz and Hegde, 2018; Taggart et al, 2020). In addition, upregulation of PPR proteins SOT1, EMB2654, PPR4 and PPR2 (which all promote chloroplast rRNA maturation), and GUN1 (implicated in the production of chloroplast ribosomal subunits RPS1 and RPL11) present further evidence of compensatory responses to reduced ribosome abundance and protein synthesis within not4a chloroplasts (Figure S6B)(Aryamanesh et al, 2017; Lee et al, 2019; Lu et al, 2011; Tadini et al, 2016; Wu et al, 2016).…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, defects in Rps8 translation due to loss of PGR3 in not4a likely explains why ribosome depletion is specific to the 30S subunit, since protein complex stoichiometries are highly regulated, with the inability to assemble complete complexes often leading to degradation of orphan subunits (Juszkiewicz and Hegde, 2018; Taggart et al, 2020). In addition, upregulation of PPR proteins SOT1, EMB2654, PPR4 and PPR2 (which all promote chloroplast rRNA maturation), and GUN1 (implicated in the production of chloroplast ribosomal subunits RPS1 and RPL11) present further evidence of compensatory responses to reduced ribosome abundance and protein synthesis within not4a chloroplasts (Figure S6B)(Aryamanesh et al, 2017; Lee et al, 2019; Lu et al, 2011; Tadini et al, 2016; Wu et al, 2016).…”
Section: Resultsmentioning
confidence: 96%
“…Nearly all PPR proteins identified to be involved in splicing in chloroplasts so far are P-class PPR proteins that appear to be primarily required for the splicing of a single, specific intron (Schmitz-Linneweber et al 2006;de Longevialle et al 2008de Longevialle et al , 2010Khrouchtchova et al 2012;Goto et al 2016;Aryamanesh et al 2017;Wang et al 2017b;Huang et al 2018;Ito et al 2018;Lee et al 2019). However, the roles of these P-class PPR proteins involved in splicing in chloroplast RNAs remain largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analysis of PPR proteins has demonstrated that chloroplast-localized maize PPR4 [ 62 ] and THA8 [ 63 ], and Arabidopsis OTP51 [ 64 ] and OTP70 [ 65 ], are essential for the splicing of chloroplast specific introns. Interestingly, recent studies of PPR4 [ 25 ], EMB2654 [ 66 ], PBF2 [ 67 ], and SOT5 [ 68 ] in Arabidopsis showed that these proteins play a role in the splicing of chloroplast introns through their role in the recognition of the specific RNA sequences. Arabidopsis HCF152 [ 69 ], MRL1 [ 70 ], PGR3 [ 71 ], BFA2 [ 72 ], and maize PPR5 [ 73 ] and PPR10 [ 74 ] were shown to be essential for the stabilization of chloroplast transcripts.…”
Section: Functions Of Ncmrbps In Plant Growth and Developmentmentioning
confidence: 99%
“…Importantly, it is now known that the nCMRBPs function as either specific RNA-binding proteins or non-specific RNA-binding proteins (RNA chaperones), which facilitates the correct folding of the target RNA structure during plant growth and under environmental stress [ 15 , 23 ]. Chloroplast- or mitochondria-localized CRM, PPR, DBRH, and SDP proteins have been assessed in terms of their roles as RNA chaperones [ 21 , 24 , 25 , 26 , 27 ]. In this review, we will focus on the recent advances in research on the function and cellular mechanisms of CRM, PPR, DBRH, and SDP proteins in organellar RNA metabolism during plant growth, development, and abiotic stress responses.…”
Section: Introductionmentioning
confidence: 99%